Linux fundamentals. (LiveLessons (Boston, Massachusetts), 2022)
10+ Hours of Video Instruction More than 10 hours of video instruction to get you up and running with Linux. Overview Linux Fundamentals LiveLessons has more than 10 hours of comprehensive video training for you to find everything you need to build a strong understanding of working with Linux. This comprehensive video course includes coverage of Linux basics, concepts, practices, and theories, so you can get the foundational knowledge of Linux you need to start your Linux career. Sander van Vugt will guide you through gaining an in-depth understanding of Linux. This full-featured video course includes a combination of active Linux demonstrations, lightboard instruction, and hands-on labs, providing a unique offering that gives you a full toolkit to enhance your learning and provide a seamless path forward should you want to get certified for Linux. This is a great first course for anyone wanting to pursue an RHCSA, Linux Foundation, or CompTIA Linux+ certification, or other entry-level Linux exams. Each lesson ends with a hands-on lab, giving you the opportunity to test out the skills and knowledge you have learned. The instructor then walks you through each Lab Solution so you can compare how you did with his work. Topics include Module 1: Essential Commands Module 2: User and Group Management and Permissions Module 3: Operating Running Systems About the Instructor Sander van Vugt has many years of experience working with, writing about, and teaching Linux and Open-Source topics. He is the author of the best-selling Red Hat RHCSA and RHCE Cert Guides as well as a number of other titles on Kubernetes (including CKAD and CKA), Ansible, Containers, Bash, Microservices, and more. Sander also works as a Linux and DevOps instructor, teaching onsite and online classes for customers around the world. Skill Level Beginner Learn How To: Install Linux Use essential tools Manage Files Work with text files Log in and run tasks with administrator privileges Work with the Bash Shell Manage Users and Groups Manage Permissions Store Management Essentials Manage networking Work with Systemd Manage software and SSH Manage Time Work with processes Schedule tasks Read log files Who Should Take This Course Administrators and developers who want to become familiar with the Linux operating system Anyone who needs basic Linux skills for working with Linux in cloud, container or Kubernetes environments Anyone taking the LFC and Linux+ exams Course Requirements Students should be able to install a virtual machine that runs Linux. Further instructions about installation are provided in Lesson 1 of this video course. About Pearson Video Training Pearson publishes expert-led video tutorials covering a wide selection of technology topics designed to teach you the skills you need to succeed. These professional and personal technology videos feature world-leading author instructors published by your trusted technology brands: Addison-Wesley, Cisco Press, Pearson IT Certification, Sams, and Que. Topics include: IT Certification, Network Security, Cisco Technology, Programming, Web Development, Mobile Development, and more. Learn more about Pearson Video training at http://www.informit.com/video.